HUBUNGAN UMUR IBU DAN PARITAS DENGAN DERAJAT LASERASI PERINEUM DI RSUD DR. R GOETENG TAROENADIBRATA PURBALINGGA - Haniyah, Siti; Adriani, Prasanti (Jurnal EDUNursing, 2019)
ABSTRACT Perineal laceration or also known as perineal rupture is one of the most often trauma suffered by women during childbirth, even during normal delivery child birth process. Laceration can be classified as mild (first and second degrees) and severe (third and fourth degrees). Perineal laceration may occur due to several factors such as age of mother and parity. Large infant head and rigid perineal muscles in primiparous can cause perineal laceration due to the perineum is not strong enough to hold the babies head strain. This research aims to determine the relationship between age of mother and parity with perineal laceration degree at dr R. Goeteng Taroenadibrata Hospital, Purbalingga. The research design uses corelation study with retrospective approach. Samples were collected using quota sampling technique. Respondents in this research were 305 mothers who gave birth spontaneously with perineal lacerations. Data was taken by performing documentation study using ssecondary data. There results of corellation between age of mother and perineal laceration degree with p-value 0,136 > ? 0,05 and corellation between parity with perineal laceration degree with p-value 0,000 < ? 0,05. The conclusions of this research are there was corellation between age of mother with perineal laceration degree and there was a significant relationship between parity with perineal laceration degree. Keywords: age of mother, parity, perineal laceration degree.